Tindak Pidana Dalam Kasus Lumpur Lapindo: Terkait Dengan Undang-Undang Nomor 32 Tahun 2009 Tentang Perlindungan Dan Pengelolaan Lingkungan Hidup - Erva Yunita; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The author raises the topic of the Lapindo mudflow case which is viewed from criminal acts related to Law Number 32 of 2009 concerning Environmental Protection and Management.. A company as a legal entity consists of many parties, including owners and directors, so that determining the party responsible for crimes related to the environment becomes complex. Regarding the Lapindo mudflow case, Lapindo Brantas Inc must be held criminally responsible and pay compensation for losses resulting from the Lapindo mudflow activities. PT was not convicted. Lapindo Brantas reflects the poor enforcement of environmental criminal law in Indonesia. It is clear that 42 experts stated that the Lapindo mudflow was not a natural disaster but was purely PT's fault. Lapindo Brantas in carrying out drilling. And the police as investigators, the prosecutor as public prosecutor and the judge who handed down the decision should try this case and punish PT. Lapindo Brantas based on Article 116 of Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) states that criminal sanctions can be imposed on business entities. To obtain answers, this research uses yuridis normative methods or library research, meaning that this research is based on on library sources to discuss the problems that have been formulated. In criminal law, criminal law can be imposed on business entities in the form of fines or administrative action, or closure of part or all of the company or in accordance with the principle of the polluter pays, but cannot be sentenced to prison because the management is a group of people. By enforcing criminal law for environmental perpetrators, the aim of punishment will be achieved, namely that the perpetrator will be deterred and will not repeat his actions and will not be imitated by others.